Esse rio é minha rua: experiências de lazer das crianças ribeirinhas da Ilha do Combu em Belém-PA - Douglas Carvalho Rocha (2021)
This study has as main objective to investigate the leisure experiences in the context of games, toys and games of riverside children from Ilha do Combu in Belém/PA. For this, we sought throughout the research to analyze the daily leisure experiences of children outside the school space, describe the games, toys and games experienced by children in different public spaces on the Island and reflect, based on leisure practices, their influences on the playful culture of children. In this context, we will situate leisure as the main category of analysis in this research, based on its understanding as a sociocultural phenomenon. As a methodological support, the observation method recorded in a field diary was used. It has a qualitative approach, with an exploratory and descriptive character, in which the study, analysis, records and interpretation of facts were carried out. For data collection, it was planned to prepare a booklet, which included tasks with questions and photographic images, in the format of homework, related to the daily activities of games, toys and games for children in the community. In the analysis, the drawings proposed in the activities and expressed in the field diary reveal different forms of entertainment, as well as different toys and games and places to play. In the answers, we can see that although there is a playful culture very unique to the Island in the children's daily leisure activities, there is also a certain urbanity in toys such as ball, captain america, teddy bear, among others, often dictated by the cultural industry, however, we observe resistance , loopholes and tactics used by some children for their leisure experiences. We conclude that the study allowed us to know the island's playful culture, its leisure experiences based on its daily relationship with the river, the forest and the universe of waters in which they are inserted. In this sense, the Island still maintains typical characteristics and aspects of riverside populations, as a specific form of social arrangement, history, economy, religion, recreational practices, as well as the use of knowledge based on experiences transmitted through its traditions and passed on from generation to generation.